Επανεξέταση και επανασχεδιασμός του βιβλίου «Γραφιστικές Εφαρμογές ΙΙ» της τρίτης Λύκειου - Γιανναπή, Κωνσταντίνα (Department of Multimedia and Graphic Arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2018)
This research targets the re-evaluation and redesign of the existing book “Graphic Application II”, that is being taught in Lyceums and Technical Schools on the island, in the past years. This book is not up-to-date since it was first published in 2000 and it has not been re-designed since then, thus it cannot serve as an optimum graphic book. On the contrary it is an old fashioned book, with outdated visual representations of different graphic examples, and there is no visual hierarchy. Furthermore, the book cover does not appeal to the age group of the students addressed. Therefore, in this study, the field of design was investigated, which is a multidimensional sector that in recent years has been on the rise in Cyprus and especially in tertiary education. In addition, a broader research has been undertaken in relation to design and education in other countries, but at the same time the essential role of visual communication in graphic design, as well as the fact that if used properly, it can attract the attention of people, and provide knowledge and visual education in youngsters. As far as the methodology followed in this study, questionnaires were given to recent school graduates from tertiary education (18+) in relation to the design and content of the book, and interviews were done with graphic designers and recent school graduates. Based on the results, a new book was redesigned. This new book is based on the text included in the already existing book, since the curriculum and the materials cannot be changed because they are instructed from the Ministry of Education. The new book is based on contemporary graphic design, it is simpler but also smaller in size and much easier for students to follow and study. Additionally, it is more appealing to the students since it has more colors and it attracts attention in this way. It’s also important to mention that the designs of the book are based on semiotics and visual communication, , that is, they are presented as allegories of a concept that carry a message that cannot visible to a bare-eye. Finally, the book was evaluated three times by different graphic designers and they were given the chance to express their views and ideas on this newly developed book, in order to be able to adapt the book to this new proposed changes and ideas. These evaluations were made using interviews and focus groups.
Keywords: Redesign, graphic design book, design education, educational book design; Επανασχεδίαση, βιβλίο γραφιστικής, εκπαίδευση στο ντιζάιν, σχεδιασμός σχολικού βιβλίου